Genetics and psychotropic drugs: present and future clinical applications - Fabbri, Chiara (Henry Stewart Talks, 2021)
Pharmacogenetics, Impact of genetics on drug response, Pharmacogenetics in psychiatry, Pharmacogenetic clinical guidelines, Pharmacogenetic testing, Drug development, Pharmacodynamics